Differentiating melanoma and healthy tissues based on elasticity-specific Brillouin microspectroscopy - Troyanova-Wood, Maria (Biomed Opt Express, 2019)
The main objective of the present study is to evaluate the use of Brillouin microspectroscopy for differentiation of melanoma and normal tissues based on elasticity measurements. Previous studies of malignant melanoma show that the lesion is stiffer than the surrounding healthy tissue. We hypothesize that elasticity-specific Brillouin spectroscopy can be used to distinguish between healthy and cancerous regions of an excised melanoma from a Sinclair miniature swine. Brillouin measurements of non-regressing and regressing melanomas and the surrounding healthy tissues were performed. Based on the Brillouin measurements, the melanomas and healthy tissues can be successfully differentiated. The stiffness of both tumors is found to be significantly greater than the healthy tissues. Notably, we found that the elasticity of regressing melanoma is closer to that of the normal tissue. The results indicate that Brillouin spectroscopy can be utilized as a tool for elasticity-based differentiation between malignant melanoma and surrounding healthy tissue, with potential use for melanoma boundary identification, monitoring tumor progression, or response to treatment.